EVALUATION OF DISTANCE EDUCATION IN DENTISTRY GRADUATION COURSE - Helbert Eustáquio Cardoso da Silva (Revista Gestão & Saúde, 2014)
The curricula of Dentistry are in the process of modernization , to suit the labor market geared to the needs of the population . The changes seek a teaching method that is conducive to student elfmanagement of their knowledge through a transdisciplinary vision. Objective: To examine about the training of teachers responsible for the disciplines of dentistry , as well as new possibilities of knowledge transmission . In this context, the distance is shown as an alternative to the continuing education of future dentists , covering new technologies and new methods of teaching adults. Methods: Through a literature review , we discuss about the goals of the national curriculum guidelines and the training of teachers of courses in dentistry and also surveys are presented in distance education in healthcare. Results: The study shows successful application of distance learning for adult learners courses in Dentistry .